Performance of Caged Broilers and Uncaged Broilers Fed with Activated Bamboo Charcoal and Bentonite Clay Mineral as Feed Additives - Cacerez, Jay Mark; Gacutan Jr., Manuel; Godinez, Cyrill John; Yap, Karen Luz (Future Science / FSH-PH Publications, 2024)
The issue of animal welfare and the usage of antibiotics resulted in the development of different rearing systems and the use of feed additives as antibiotic alternatives. Cage-free broiler production allows birds to express their normal behavior promoting better welfare of the animal. The study aimed to investigate the growth performance of broiler chickens reared in cages and uncaged with feed additives. A total of 180 COBB broilers were used and randomly distributed into 6 different treatments and replicates following a randomized complete block design. The birds were weighed prior to arrival, 1st week, 2nd week, 3rd week, 4th week, and 5th week to determine the growth performance parameters. Economic analysis was also measured after the end of the study. The data was analyzed using Proc Mixed of SAS v. 9.4, and group comparison was used to evaluate the differences between the control and experimental groups. The result showed significant differences in feed intake at 1st week (p=0.0249) compared to the birds reared in an uncaged system. Feed intake in subsequent weeks and other growth performance parameters showed no significant differences throughout the study. Birds fed with 0.5% activated bamboo charcoal and bentonite clay obtained a higher return on investment than in 1% inclusion. These results imply that uncaged birds have the same growth performance with caged birds and could express their natural behavior at the same time. The result also revealed that better performance and profitability can be achieved at 0.5% inclusion of feed additives in the diet.